(untitled) (Journal of the College of Basic Education, 2022)
The spectrum attenuation of free space optical (FSO) communication systems operating at visible and near infrared (NIR) wavelengths (650nm , 850nm and 1550) under dust was experimentally investigated. Dust are generated and controlled homogeneously along a dedicated atmospheric chamber of (93*63*60)cm dimensions. Attenuation due to aerosols restricts the distance of FSO communication systems and limits the availability for line-of-sight terrestrial link. This work is focused on the effect of aerosols on the FSO link. The attenuations was studied in the aerosols phenomena for three selected wavelengths (650, 850, and 1550 nm( for transmitting range (1-12) Km.